Sensory features and physicalchemical characterization of brazilian honey bread with passion fruit peel flour - Conti-Silva, Ana Carolina [UNESP]; Ferreira Roncari, Renata [UNESP] (Emerald, 2015)
Purpose – The purpose of this paper is to substitute wheat flour by passion fruit peel flour in Brazilian honey bread (pão de mel), with evaluation of the breads’ sensory features, chemical composition and physical properties. Design/methodology/approach – Honey breads with wheat flour (standard) and with replacement  of this ingredient by 10 to 50 per cent passion fruit peel flour were produced. Two sensory tests were applied, to identify how different formulations with passion fruit peel flour were when compared to the standard formulation, and also the acceptability of the products. The selected honey breads, through sensory results, were evaluated regarding to chemical composition and physical properties. Findings – Formulations with 10 and 20 per cent substitution were the least different to formulations with only wheat flour, and were as acceptable as the wheat flour sample. Physical and chemical characteristics of breads with 10 and 20 per cent passion fruit peel flour were similar; however, honey bread with 20 per cent passion fruit peel flour had higher fibre content, ash quantity and hardness value; a lower specific volume; and a different colour from the wheat flour sample. Practical implications – This study offers an opportunity to food industries through utilization of an agro-industrial by-product on the formulation of a Brazilian traditional product. Originality/value – This study presents the feasibility of using an agro-industrial by-product to Brazilian honey bread, enhancing the nutritive value of this product and reducing the impact of passion fruit peel flour on the environment.
Keywords: Consumers; Product development; Sensory attributes